Aromatic Hydroxyketones Preparation and Physical Properties - Martin, Robert (Springer Netherlands Imprint: Springer, 2011)
Aromatic Hyroxyketones: Preparation and Physical Properties is a revised, new edition 4-volume handbook set which provides detailed information on physical properties and syntheses on a wide range of hydroxyketones. Each entry includes characterization data such as the Chemical Abstracts Service Registry Number (CAS RN), molecule name, molecular formula, and molecular weight. The handbooks are presented in dictionary style, with a logical classification of the ketones, making the information easily available for consultation. This handbook set provides 6000 hydroxyketone entries and includes approximately 6000 references. Volume 1: Hydroxybenzophenones Hydroxybenzophenones are most useful synthetic intermediates in the chemical industry, for example in pharmaceuticals, dyes, fragrances, agrochemicals, explosives and plastics. The first volume of this set is particularly intended for engineers in chemical synthesis and academics as well as industrial researchers from various branches of chemistry. Volume 2 and 3: Hydroxyacetophenones Hydroxyacetophenones constitute the starting material for a wide variety of syntheses in organic chemistry. They are versatile building blocks serving many different applications, such as especially polymers, pharmaceuticals and fine chemicals. These two volumes constitute a useful tool for chemists and pharmacists in general. Volume 4: Hydroxypropiophenones, Hydroxyisobutyrophenones, Hydroxypivalophenones and Derivatives Hydroxypropiophenones, Hydroxyisobutyrophenones, Hydroxypivalophenones and Derivatives constitute the starting material for a wide variety of syntheses in organic chemistry. They are versatile building blocks serving many different applications: pharmaceuticals, fine chemicals and polymers. This volume is a great book of reference on hydroxypropiophenones, hydroxyisobutyrophenones, hydroxypivalophenones and their methyl ethers which also mentions some uses of these ketones. It is a powerful synthesis tool for researchers or industrial producers and provides a wide choice of hydroxyketones.